Small and Medium-sized Enterprises, and Business Uncertainty Just Surviving or Thriving? - Adapa, Sujana; McKeown, Tui.; Lazaris, Miria; Jurado, Tanya (Singapore : Springer Nature Singapore : Imprint: Palgrave Macmillan, 2023)
Research in this book enhances the understanding of small and medium-sized businesses as a result of unprecedented challenges presented to them. It elaborates on how some small and medium-sized businesses not only survive, but also thrive amidst uncertainties, by embracing digital solutions or transformations. To achieve this, the book adopts mixed research methods, with a combination of case studies, secondary data analysis and primary data analysis (survey information and/or interviews). Tables and illustrations are also included to provide the reader with a holistic understanding of small and medium-sized businesses from different cultural contexts. Dr Sujana Adapa is a Professor in Management and Head of UNE Business School at the University of New England, Australia. Her research interests covers areas in Marketing and Management, with a focus on entrepreneurship, technology adoption, sustainable practices, gender studies and leadership. She has led funded research projects on future of work, small business management, leadership and sustaining diversity. Dr Tui McKeown is an Associate Professor who works in the Monash Business School at Monash University, Australia. Her research interests are in entrepreneurship, small businesses, changing world of work and nonstandard employment. She is an active researcher and her work has been published in reputable journals with high quality. She has also led several research projects on modernizing workplaces, work integrated learning dignity, and future of work. Dr Miria Lazaris completed her PhD in International Business at Monash University in 2011. Her research examined the internationalisation of SMEs operating in the Australian food and beverage sector. Miria's research and consulting interests continue to include the activities of Australian organisations, particularly SMEs. Miria currently teaches for the Department of Management at Monash University, Australia. Dr Tanya Jurado is a Senior Lecturer in the School of Management, Massey University, New Zealand. Her research focus is on the role of SMEs amidst the global challenges faced by economies worldwide and gender inclusion in IT professions. She is currently working on projects exploring SME internationalisation, indigenous entrepreneurship and public policy support for SMEs.
Chapter 1: MSMEs and SDGs - Narratives from India -- Chapter 2: Unravelling the impact of COVID-19 on SMEs: A review of emerging literature -- Chapter 3: A conceptual framework for an integrated one stop portal to support indigenous small business enterprises -- Chapter 4: Is knowledge Ambidexterity the answer to economic sustainability for SMEs? Lessons learned from digitalisation efforts during the COVID-19 pandemic -- Chapter 5: Insights from the Australian SMEs during the pandemic -- Chapter 6: SME sentiments, access to government support, and resilience during a pandemic -- Chapter 7: Entrepreneurial ecosystem in India -- Chapter 8: SMEs and free trade agreements: Engagement and policy development -- Chapter 9: Pandemic speed: Accelerating innovation in cyber security -- Chapter 10: A conceptual framework for restaurants to recover from COVID-19 pandemic -- Chapter 11: Narratives of being rural, female and an entrepreneur in Australia -- Chapter 12: What all small business owners want to know - 'What is my business really worth?'.
Keywords: Small business; Entrepreneurship; New business enterprises; Family-owned business enterprises; Small Business; Entrepreneurship; Family Business